William Allen papers - Allen, William, 1803-1879.
Correspondence, memoranda, speeches, financial records, scrapbooks, printed material, maps, and other papers relating chiefly to Allen's service as U.S. senator and representative from and governor of Ohio. Includes material concerning the greenback movement, land surveys, the Mexican War, national and Ohio state politics, the Oregon question, and the annexation of Texas. Includes records of the Ohio Militia Chillicothe Independent Blues and of the Stoney Mill Salt Works (Chillicothe, Ohio). Correspondents include James John Faran, James Graham, John Hough, Amos Layman, George Morgan, and Henry A. Whitman.
Lawyer, farmer, and U.S. representative and senator from and governor of Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Faran, James John, -- 1808-1892 -- Correspondence; Graham, James, -- 1793-1851 -- Correspondence; Hough, John, -- active 1831-1845 -- Correspondence; Layman, Amos -- Correspondence; Morgan, George, -- 1777-1846 -- Correspondence; Whitman, Henry A. -- Correspondence; Ohio. -- Militia. -- Chillicothe Independent Blues; Stoney Mill Salt Works; Greenbacks; Mexican War, 1846-1848.; Oregon question; Salt industry and trade -- Ohio -- Chillicothe; Northwest boundary of the United States; Ohio -- Politics and government -- 1787-1865.; Ohio -- Surveys; Oregon -- Boundaries; Oregon Territory -- History; Texas -- Annexation to the United States; United States -- Politics and government -- 1815-1861.; Farmers; Governors -- Ohio; Lawyers; Representatives, U.S. Congress -- Ohio; Senators, U.S. Congress -- Ohio